Different Grouping Strategies for Cooperative Learning in English Majored Seniors and Juniors at Can Tho University, Vietnam - Hien Nhan; Thái Anh Nhan (MDPI AG, 2019)
We present research on the attitudes of seniors and juniors doing a major in English toward different grouping strategies for cooperative learning at Can Tho University, Can Tho city, Vietnam. The collected data is analyzed by a means of quantitative approach. The findings not only facilitate the further understanding of English majors’ opinions on different grouping strategies, but also provide teachers and lecturers who employ cooperative learning as one of their teaching strategies with useful clues on which group formation they should use. More importantly, we hope to give an insight to the characteristics of different grouping strategies, in order to find out the group forming method(s) that simultaneously boosts group dynamics, students’ satisfaction, and academic achievements.